Umpolung in a Pair of Cobalt(III) Terminal Imido/Imidyl Complexes - Mao, Weiqing; Fehn, Dominik; Heinemann, Frank Wilhelm; Scheurer, Andreas; Van Gastel, Maurice; Jannuzzi, Sergio A.; Debeer, Serena; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2022)
Reaction of the CoI complex [(TIMMNmes)CoI](PF6) (1) (TIMMNmes=tris-[2-(3-mesityl-imidazolin-2-ylidene)-methyl]amine) with mesityl azide yields the CoIII imide [(TIMMNmes)CoIII(NMes)](PF6) (2). Oxidation of 2 with [FeCp2](PF6) provides access to a rare CoIII imidyl [(TIMMNmes)Co(NMes)](PF6)2 (3). Single-crystal X-ray diffractometry and EPR spectroscopy confirm the molecular structure of 3 and its S= (Formula presented.) ground state. ENDOR, X-ray absorption spectroscopy and computational analyses indicate a ligand-based oxidation; thus, an imidyl-radical electronic structure for 3. Migratory insertion of one ancillary NHC to the imido ligand in 2 gives the CoI N-heterocyclic imine (4) within 12 h. Conversely, it takes merely 0.5 h for 3 to transform to the CoII congener (5). The migratory insertion in 2 occurs via a nucleophilic attack of the imido ligand at the NHC to give 4, whereas in 3, a nucleophilic attack of the NHC at the electrophilic imidyl ligand yields 5. The reactivity shunt upon oxidation of 2 to 3 confirms an umpolung of the imido ligand.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Cobalt; Imidyl Radical; N-Heterocyclic Carbene; Terminal Imido; Umpolung